Back Cover: AKT1/HK2 Axis‐mediated Glucose Metabolism: A Novel Therapeutic Target of Sulforaphane in Bladder Cancer. Issue 3 (2nd February 2022) - Huang, Lei; He, Canxia; Zheng, Sicong; Wu, Chao; Ren, Minghua; Shan, Yujuan
Abstract : Mol. Nutr. Food Res . 2022, 66, 202100738 DOI: 10.1002/mnfr.202100738 A unique characteristic of glucose transport aberrant‐independent aerobic glycolysis exists in bladder cancer patients, and the lower grade malignant tissues have the more obvious abnormality. Sulforaphane, an isothiocyanate derived from glucosinolates in cruciferous vegetables, has been proven to inhibit glycolysis and mitochondrial oxidative phosphorylation via blocking of the AKT1/HK2 axis and PDH expression, especially in low grade tumor cells. This is reported by Minghua Ren, Yujuan Shan, and co‐workers in article number 2100738 .